Analisis Kesalahan Penyelesaian Soal Cerita Berdasarkan Kriteria Watson - Sri Hariyani; Fitria Nur Kusti Aisyah; Riski Nur Istiqomah Dinullah (JRPM (Jurnal Review Pembelajaran Matematika), 2019)
This study aims to analyze errors by students in problem-solving of mathematical story based on Watson criteria. The subjects of this study were two high-ability students, two moderate-ability students, and two low-ability students. This study at class VII-C SMP NU Sunan Giri Kepanjen. The instruments used are written tests and interviews — the validity of the data checking by the triangulation of sources that compare test results and interview data. Data analysis used is data reduction, data presentation, and conclusions. The students' errors were analyzed using the Watson error category, which consisted of 8 errors. The results showed that based on Watson's error criteria, the mistakes that occurred were inaccurate data, improper procedures, skill hierarchy problems, missing data, nothing manipulation directly, conflict level response, missing conclusions and in addition to the seven categories. The results of this study are expected to be an input for the teacher about the types of student's errors at SMP Sunan Giri Kepanjen.